Peran Inspektorat Dalam Pelaksanaan Sistem Pengendalian Intern Pemerintah Pada Pemerintah Daerah Kabupaten Kepulauan Talaud - Manialup, Angel Wulandari; Nangoi, Grace B; Morasa, Jenny (Universitas Sam Ratulangi, 2017)
Abstract. Government Internal Control system is a system of internal control implemented whole in the central government and local government. If the Government Regulation Number 60 year 2008 is performed effectively, it will support to minimize the occurrence of oversights.Â The purposes of this research are : (1) To find out the roles of Inspectorate in the implementations of GICS in Talaud Islands Regency; (2) To analyze the challenges and difficulties that affect the Inspectorate roles in the implementation ofÂ Government Internal Control System (GICS) in Talaud Islands Regency; (3) To analyze the Inspectorate efforts to improve the implementation of GICS in Talaud Islands Regency. This study is a qualitative exploratory research. Data were collected through interviews, observation, and documentation study. Data consists of primary and secondary data. The interviews were transcribed, analyzed, coded and categorized into themes. Data was analysed by content analysis. The research findings show that Inspectorate holds important roles in GICS Implementation in Talaud Regency, such as leadership, internal control, consultancy and quality assurance. Difficulties influence the Inspectorate roles in GICS implementation in Talaud Regency are: the absence of both regent regulation and the organization of GICS task force, inadequate human resources understanding of GICS and lack of membership, insufficient budget for control activities, inexistence of joint commitment in implementing GICS as well as risk assessment and non-optimal risk planning due to time limitations. Efforts conducted by Inspectorate in order to improve the Implementation of GICS in Talaud Regency are to suggest the frame of regent regulation and GICS task unit, improve the quality of resources through education, trainings, technical seminar or office training, counselling, coordinate the education improvement with many institutions such as BPKP, add extra budgeting for control activities, establish joint commitment in GICS implementation, carry out risk assessment and risk planning optimally and develop effective communication with SKDP as well as BPKP.Keywords:Â The role of Inspectorate, GICS implementation, difficulties, effortsAbstrak. Sistem Pengendalian Intern Pemerintah adalah Sistem Pengendalian Intern yang diselenggarakan secara menyeluruh di lingkungan pemerintah pusat dan pemerintah daerah. Peraturan Pemerintah No. 60 tahun 2008 tentang SPIP jika dilakukan dengan efektif akan sangat membantu untuk meminimalisir risiko terjadinya kesalahan. Penelitian ini bertujuan untuk : (1) Mengetahui bagaimana peran Inspektorat dalam pelaksanaan Sistem Pengendalian Intern Pemerintah (SPIP) di Kabupaten Kepulauan Talaud; (2) Menganalisis kendala-kendala yang mempengaruhi peran Inspektorat dalam pelaksanaan SPIP di Kabupaten Kepulauan Talaud; (3) Menganalisis upaya-upaya yang dilakukan Inspektorat untuk meningkatkan pelaksanaan SPIP di Kabupaten Kepulauan Talaud. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan eksploratori. Pengumpulan data dilakukan melalui wawancara, observasi dan studi dokumentasi. Terdiri dari data primer dan data sekunder. Hasil wawancara ditranskrip menjadi transkrip data, kemudian dianalisis, diberi kode, dan dikategorikan ke dalam tema. Analisis data menggunakan analisis isi. Hasil penelitian menunjukkan bahwa Peran Inspektorat dalam pelaksanaan SPIP di Kabupaten Kepulauan Talaud yaitu dalam hal kepemimpinan, pengawasan intern, konsultan dan penjamin mutu. Kendala-kendala yang mempengaruhi peran Inspektorat dalam pelaksanaan SPIP di Kabupaten Kepulauan Talaud yaitu belum adanya Peraturan Bupati dan belum membentuk Satuan Tugas SPIP, pemahaman SDM akan SPIP masih kurang dan jumlah personil belum memadai, anggar kegiatan pengawasan kurang memadai, belum ada komitmen bersama dalam melaksankan SPIP serta penilaian risiko dan pemetaan risiko belum optimal karena keterbatasan waktu. Upaya-upaya yang dilakukan Inspektorat untuk meningkatkan pelaksanaan SPIP di Kabupaten Kepulauan Talaud adalah dengan mengusulkan penyusunan Peraturan Bupati dan pembentukan Satuan Tugas SPIP, meningkatkan kualitas sumber daya, melalui jenjang pendidikan, diklat-diklat, pelatihan kantor sendiri, pembinaan, melakukan koordinasi meningkatkan pendidikan dengan lembaga-lembaga seperti BPKP, menambah anggaran kegiatan pengawasan, membangun komitmen bersama dalam melaksanakan SPIP, melakukan penilaian risiko dan pemetaan risiko secara optimal dan membangun komunikasi yang efektif dengan SKPD maupun BPKP.Kata kunci: Peran Inspektorat, pelaksanaan SPIP, kendala, upaya